(untitled) (Revista de Artes Marciales Asiáticas, 2026)
This study investigated the relationship between variables of the deep squat jump (DSJ) and the Abalakov jump (ABK) and the performance of the rear leg roundhouse kick in elite combat sport athletes. Twenty-seven elite taekwondo athletes (12 females) performed three attempts of each movement: DSJ and ABK (measured with Pasco® force platforms), and the roundhouse kick (analyzed with Vicon® motion capture systems). The key findings demonstrated that specific force and power metrics from the jumps are significant predictors of kicking kinematics. For the DSJ, the rate of force development (RFD) in the first 100 ms of the concentric phase (RFDcon) was a primary predictor, independently explaining 21% of the variance in linear foot velocity (p=0.009) and 30.3% in linear foot acceleration (p=0.003). Furthermore, for the non-dominant (stance) limb, takeoff peak force independently predicted angular hip acceleration (R²=0.144, p=0.029). For the ABK, the eccentric braking RFD at 100 ms (RFDecc) emerged as a strong predictor, accounting for 24% of the variance in angular hip acceleration (p=0.006). In conclusion, this study validates the DSJ and ABK as practical tools for assessing qualities critical to roundhouse kick performance. Coaches should prioritize monitoring RFDcon and stance limb strength during a DSJ, as well as the RFDecc during an ABK, to evaluate and train for improved kicking power.